SYNTHESIS AND CHARACTERIZATION OF NANO HYDROXYAPATITE WITH PECTIN CITRUS (BIO-POLYMER) FOR BIOMEDICAL APPLICATION - K. SENTHILARASAN; P. SAKTHIVEL (International Journal of Pharma and Bio Sciences, 2015)
Hydroxyapatite (HAp) is a biocompatible ceramic that is widely used in a number of biomedical applications and devices. Due to the close similarity between nanometer scale forms of HAp and the mineral phase found in the natural bone matrix, it has gained increased importance in recent years. Pectin is a naturally occurring polysaccharide. The benefits of pectin are appreciated by scientists due to its biodegradability. HAp/PC nano composite could be more useful for treatment of oral bone defects in comparison with conventional of nHAp/Pc and could be more effective as a bone replacement material to promote bone formation. FTIR, XRD, TEM, TG/DTA was used to identify the functional groups, phase structure, morphology and thermal stability of the synthesized composite. The result of these studies indicated that the powders were biocompatible and would not cause toxic reactions. This powder sample could be applied for biomedical application.